Single Nucleotide Polymorphisms of Cytotoxic T-lymphocyte Antigen 4 (CTLA-4) and Susceptibility to Chronic Viral Hepatitis B and C Infections (Journal of Renal and Hepatic Disorders, 2018)
The cytotoxic T-lymphocyte antigen 4 (CTLA-4) gene is a negative regulator of T-lymphocyte activation and proliferation. Single nucleotide polymorphisms (SNPs) occurring on the CTLA-4 gene can modify the ability to control the proliferation of T-lymphocytes, thereby impacting the clearance of hepatitis B (HBV) and hepatitis C (HCV) virus infections. The −319C/T and +49A/G SNPs of CTLA-4 gene have been associated with autoimmune disorders and liver infections. Studies show that the +49G allele confers susceptibility to HBV and HCV infections in chronic disease (without cirrhosis), associates with the risk of chronic HCV infection in males, confers protective effect against the development of hepatocellular carcinoma, and favors viral elimination. Furthermore, the +49G allele alone or in haplotype with the −319C favors chronic infection with genotype 3 HCV, has an inverse association with HCV genotype 1, and decreases viral load in chronic hepatitis C associated with sustained virological response (SVR). These findings support an important role of the SNPs of CTLA-4 gene in viral hepatitis; however, the mechanisms by which they influence immune response against viral infections are not fully understood. This review gives an overview of the current understanding of the association between CTLA4 SNPs and HBV/HCV infections.
Keywords: Cytotoxic T-lymphocyte antigen 4; CTLA-4; Hepatitis C virus; Hepatitis B virus; single nucleotide polymorphisms